The Managerial Roles of Leaders of Pesantren-Based Rehabilitation Institutions in Overcoming Juvenile Delinquency - DZ, Abdus Salam; Kulkarni, Shirin; Karim, Abdul; Muhammadun, Muhammadun; Jalaludin, Jalaludin (JURNAL AL-TANZIM, 2024)
This study aims to explore the managerial role of leaders of pesantren-based rehabilitation institutions in tackling juvenile delinquency in Pondok Bukit Mahabbah Darul Adni majalengka, and its impact on the character and mental development of students. This research was conducted through in-depth interviews, participatory observation, and document analysis using qualitative case study methods. A thematic analysis approach was applied to identify key themes from the data collected over the six-month research period. The results of this study show that institutional leaders have successfully carried out managerial roles in tackling juvenile delinquency originating from various regions in Indonesia, which is reflected. This is reflected in the interpersonal role of the leader of the institution, the informational role and the decisional role performed by the leader of the institution in carrying out its institutional management. This research opens up opportunities for further study on juvenile delinquency handling in other educational institutions and broadens the scope of research on the managerial role of agency leaders in tackling juvenile delinquency